Integrated lithium battery negative plate with cross-linked conductive carbon skeleton structure
Through the hydrogen bonding of bacterial cellulose with active materials and graphene oxide, an integrated lithium battery negative electrode sheet with cross-linked conductive carbon framework structure is constructed, which solves the problems of poor conductivity and unstable structure of traditional lithium battery negative electrodes, and achieves a lithium battery negative electrode with high surface capacity and cycling stability.
Patent Information
- Application Number
- CN202411929060.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The negative electrode of traditional lithium-ion batteries has problems such as poor conductivity and unstable carbon frame structure, which affects its cyclic stability.
The characteristics of hydrogen bonding between bacterial cellulose, lithium-ion battery active materials and graphene oxide were adopted to form an integrated lithium battery negative electrode sheet with a crosslinked conductive carbon framework structure through solution self-assembly combined with vacuum suction filtration and thermal reduction strategies.
The conductivity and cycle stability of the lithium battery negative electrode are improved, and a high-face capacity lithium battery negative electrode without metal current collector, conductive agent and binder is achieved.
Smart Images

Figure CN119725386A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to an integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure. Background Art
[0002] Lithium-ion battery is a kind of energy storage device that uses compounds that can embed lithium ions as positive and negative electrode materials. Lithium ions shuttle back and forth through electrolytes to achieve energy storage and release. Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, separators, electrolytes, current collectors and shells. Among them, the positive and negative electrodes are the core of the entire battery. The positive and negative active materials are mainly used to store lithium ions, and their performance directly determines the quality of the battery's energy storage characteristics.
[0003] In order to increase the surface capacity of lithium-ion negative electrodes and thus realize the construction of high-energy-density lithium-ion batteries, the mass proportion of active materials in the negative electrode should be increased as much as possible. In traditional lithium-ion batteries, the mass proportion of metal current collectors (including copper foil and aluminum foil) is as high as 15% (Advanced Energy Materials, 2019, 9: 1901457; Joule, 2021, 5(6): 1301-1305), which seriously restricts the improvement of lithium-ion battery energy density. Therefore, with the help of sophisticated structural design, the negative electrode active materials are evenly dispersed in the highly conductive skeleton material to construct an integrated lithium-ion negative electrode without using a current collector and without adding additional conductive agents and binders. This is an effective way to construct a high-surface capacity lithium-ion negative electrode. However, compared with the lithium-ion negative electrode prepared by coating the electrode material on the copper current collector, the integrated lithium-ion negative electrode usually has the problem of poor conductivity and structural instability of the carbon skeleton under the huge volume stress of the active material, which in turn affects its cycle stability. Summary of the invention
[0004] The purpose of the present invention is to provide an integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure, which solves the practical problems of how to improve the conductivity of the integrated lithium battery negative electrode and maintain the structural stability of the carbon skeleton under the huge volume stress of the active material. The property of hydrogen bonding between bacterial cellulose and negative electrode active material particles and graphene oxide is utilized, and the solution self-assembly combined with vacuum filtration and thermal reduction strategy is adopted to construct an integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure, so that the integrated lithium battery negative electrode achieves cycle stability.
[0005] An integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure, the specific preparation method comprises the following steps:
[0006] Step S1: dispersing bacterial cellulose in deionized water to prepare a bacterial cellulose dispersion;
[0007] Step S2: dispersing the lithium ion battery active material into deionized water to prepare an active material dispersion;
[0008] Step S3: adding the active material dispersion obtained in step S2 dropwise to the bacterial cellulose dispersion obtained in step S1, and stirring in a water bath at room temperature for 5 hours;
[0009] Step S4: dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion;
[0010] Step S5: adding the graphene oxide dispersion obtained in step S4 dropwise to the solution obtained in step S3, and continuing to stir in a water bath at room temperature for 5 hours;
[0011] Step S6: vacuum filter the dispersion obtained in step S5, wash and dry to obtain a self-supporting film;
[0012] Step S7: placing the self-supporting film obtained in step S6 under an inert atmosphere and carbonizing it at high temperature for 2 hours to obtain an integrated lithium battery negative electrode sheet having a cross-linked conductive carbon skeleton structure;
[0013] In step S1, the dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring, or a combination of these;
[0014] In step S2, the dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring, or a combination of these;
[0015] In step S4, the dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring, or a combination of these;
[0016] In the step S1, the concentration of the bacterial cellulose dispersion is 0.1-2.5 mg / mL.
[0017] In step S2, the concentration of the active material dispersion is 1-10 mg / mL, and the active material includes silicon (Si), silicon dioxide (SiO X ), tin (Sn), bismuth (Bi) and other common lithium battery negative electrode materials or a mixture of them;
[0018] In the step S4, the concentration of the graphene oxide dispersion is 1-10 mg / mL;
[0019] In the step S7, the high temperature carbonization temperature range is 700-1100°C. The high temperature carbonization process converts bacterial cellulose into conductive carbon fibers (PBFs), removes oxygen-containing functional groups on the surface of graphene oxide, and improves the conductivity of the electrode sheet.
[0020] In step S7, the integrated lithium battery negative electrode sheet has a self-supporting structure and does not require the use of a metal current collector; no conductive agent or adhesive is required during the preparation process; and the graphene sheets in the integrated lithium battery negative electrode sheet are cross-linked and the PBFs fibers are arranged throughout, forming a cross-linked conductive carbon skeleton with a multi-porous structure; and the active material in the integrated lithium battery negative electrode sheet is anchored to the cross-linked conductive carbon skeleton through covalent bonds.
[0021] It should be noted that the conductive carbon fiber and PBFs fiber mentioned in this scheme are actually the same substance. For the sake of adaptability, they are described in different ways in different regions. This does not affect the understanding and implementation of this scheme. This is hereby explained.
[0022] This scheme develops a cross-linked conductive carbon skeleton with good mechanical flexibility, and loads lithium battery negative electrode materials such as silicon and silicon monoxide onto the cross-linked conductive carbon skeleton to construct an integrated lithium battery negative electrode without the need for additional conductive agents and binders. The cross-linked conductive carbon skeleton can "breathe and exhale" following the volume "expansion and contraction" of the active material during the lithium insertion / delithiation process, thereby improving the cycle stability and rate performance of the lithium battery negative electrode.
[0023] The beneficial effects of the present invention are as follows:
[0024] (1) The present invention utilizes the property of hydrogen bonding between bacterial cellulose and lithium-ion battery active materials and graphene oxide, and constructs an integrated lithium battery negative electrode sheet through solution self-assembly combined with vacuum filtration and thermal reduction strategies; the graphene sheets in the integrated lithium battery negative electrode sheet are cross-linked, and highly conductive PBFs fibers run through them, forming a cross-linked conductive carbon skeleton structure in the electrode, which provides a three-dimensional conductive network for the transmission of electrons in the electrode, greatly improving the electronic conductivity of the electrode.
[0025] (2) The highly conductive PBFs fibers act as a support, constructing an effective lithium ion transmission channel in the electrode and an appropriate buffer space to accommodate the volume change of the active material. At the same time, the active material is anchored to the cross-linked conductive carbon skeleton through covalent bonds. The cross-linked conductive carbon skeleton can reversibly expand and contract with the lithiation and delithiation of the active material, which not only improves the electron transmission capacity of the lithium battery negative electrode, but also solves the problem of the separation of the active material from the conductive network during the electrochemical cycle, thereby improving the cycle stability and rate characteristics of the lithium battery negative electrode.
[0026] (3) The integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure in this scheme has a self-supporting structure, does not require the use of a metal current collector, and does not require the addition of commercially common conductive agents such as acetylene black during the preparation process. It does not require the addition of commercially common binders such as polyvinylidene fluoride (PVDF), which greatly increases the proportion of active materials in the electrode and has great potential for constructing a high surface capacity lithium battery negative electrode.
[0027] (4) The cross-linked conductive carbon skeleton structure developed in this scheme has universal adaptability and is suitable for silicon (Si), silicon dioxide (SiO X ), tin (Sn), and other lithium-ion battery active materials with large volume strain. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Flow chart of the method of Example 1 of the present invention.
[0029] Figure 2 A scanning electron microscope photograph of the self-supporting film obtained in Example 1 of the present invention.
[0030] Figure 3a A cross-sectional scanning electron microscope photograph of the integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure obtained in Example 1 of the present invention.
[0031] Figure 3b Fourier transform infrared spectrum of the integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure obtained in Example 1 of the present invention.
[0032] Figure 4 A cross-sectional scanning electron microscope photograph of the integrated lithium battery negative electrode sheet with graphene as the conductive carbon skeleton obtained in Comparative Example 1 of the present invention.
[0033] Figure 5 A comparison chart of the cycle performance of the lithium-ion batteries prepared in Example 1 and Comparative Example 1 of the present invention.
[0034] Figure 6 A comparison of the electronic conductivity of Example 1 and Comparative Example 1 in the present invention. DETAILED DESCRIPTION
[0035] In order to more clearly illustrate the technical features of this solution, this solution is described below through specific implementation methods.
[0036] Example 1
[0037] The preparation process of Example 1 of the present invention is as follows: Figure 1 The preparation method of the integrated lithium battery negative electrode sheet with nano-silicon as the active material and a cross-linked conductive carbon skeleton structure includes the following steps:
[0038] Step 1: Disperse 10 mg of bacterial cellulose (BC) in 20 mL of deionized water using a high-speed shear homogenizer to obtain a bacterial cellulose dispersion;
[0039] Step 2: 54 mg of nano-Si (particle diameter distribution range is 30-100 nm) and 36 mg of graphene oxide (GO) were ultrasonically dispersed in 20 mL of deionized water to obtain nano-Si dispersion and graphene oxide dispersion, respectively;
[0040] Step 3: adding the nano-Si dispersion dropwise into the bacterial cellulose dispersion, and stirring in a water bath at room temperature for 5 hours to obtain a Si / bacterial cellulose dispersion in which bacterial cellulose anchors Si particles;
[0041] Step 4: adding the graphene oxide dispersion dropwise into the Si / bacterial cellulose dispersion, and continuing to stir in a water bath at room temperature for 5 hours to obtain a dispersion of bacterial cellulose cross-linked graphene and Si particles;
[0042] Step 5: The above dispersion is vacuum filtered, washed and dried to obtain a self-supporting film. In the obtained self-supporting film, bacterial cellulose firmly cross-links the graphene oxide and the Si particles. Figure 2 As shown;
[0043] Step 6: In order to enhance the conductivity of the self-supporting film, the self-supporting film is placed in a nitrogen atmosphere and carbonized at 800°C for 2 hours to obtain an integrated lithium battery negative electrode sheet with nano-silicon as the active material and a cross-linked conductive carbon skeleton structure.
[0044] In the lithium battery negative electrode sheet, graphene (G) sheets are interwoven, and bacterial cellulose pyrolysis carbon fibers (PBFs) are arranged throughout, and together with the spatially interwoven graphene, a multi-layer conductive carbon skeleton with a multi-porous structure is formed, such as Figure 3a During the carbonization and pyrolysis process, covalent Si-OC bonds are formed between the nano-Si particles and the cross-linked conductive carbon skeleton, as shown in Figure 3b As shown, the nano-Si particles are firmly anchored on the cross-linked conductive carbon skeleton.
[0045] Comparative Example 1
[0046] Without adding bacterial cellulose, an integrated lithium battery negative electrode sheet with nano-silicon as active material and graphene as conductive carbon skeleton is prepared. The preparation method includes the following steps:
[0047] Step 1: 54 mg of nano-Si (particle diameter distribution range is 30-100 nm) and 36 mg of graphene oxide (GO) were ultrasonically dispersed in 20 mL of deionized water to obtain nano-Si dispersion and graphene oxide dispersion, respectively;
[0048] Step 2: adding the graphene oxide dispersion dropwise into the Si dispersion, and continuing to stir in a water bath at room temperature for 5 hours to obtain a dispersion of graphene and Si particles;
[0049] Step 3: vacuum filter the above dispersion, wash and dry it to obtain a self-supporting film;
[0050] Step 4: Place the self-supporting film in a nitrogen atmosphere and carbonize it at 800 °C for 2 hours to obtain an integrated lithium battery negative electrode sheet with nano-silicon as the active material and graphene as the conductive carbon skeleton.
[0051] Comparative Example 1 In the negative electrode sheet of lithium battery, graphene sheets are stacked, and Si particles are agglomerated into aggregates, such as Figure 4 shown.
[0052] Example 2
[0053] SiO X The nanoparticles are active materials, and the integrated lithium battery negative electrode sheet has a cross-linked conductive carbon skeleton structure. The preparation method includes the following steps:
[0054] Micron-sized silicon dioxide (SiO X ) was crushed and sieved to obtain SiO X Nanoparticles (particle diameter distribution range 30-100 nm), as described in Example 1, using an equal mass of SiO X Nanoparticles are substituted for Si nanoparticles, and the rest of the process is the same as in Example 1 to obtain SiO X Nanoparticles are active materials and are integrated into a lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure.
[0055] Comparative Example 2
[0056] SiO X The integrated lithium battery negative electrode sheet with nanoparticles as active materials and graphene as conductive carbon skeleton is prepared by the following steps:
[0057] In the process described in Comparative Example 1, an equal mass of SiO X Nanoparticles replace Si nanoparticles, and the rest of the process is the same as in Comparative Example 1 to obtain SiO X An integrated lithium battery negative electrode sheet with nanoparticles as active materials and graphene as the conductive carbon skeleton.
[0058] The above four lithium battery negative electrode sheets were cut into pieces and assembled into button-type half-cells, and the electrochemical cycle performance test was carried out. First, they were activated for 3 cycles at a current density of 0.1 A / g, and then their cycle performance was tested at a current density of 0.5 A / g. The test results are shown in Table 1. The electrochemical cycle performance test results of Example 1 and Comparative Example 1 are shown in Table 1. Figure 5 shown.
[0059] After 200 cycles of charge and discharge at 0.5 A / g, the surface capacity of Example 1 is still as high as 3.5 mAh / cm-2 , still meets the requirements for the surface capacity of lithium battery negative electrode in commercial application, while the surface capacity of Example 1 under the same conditions is only 0.7 mAh / cm -2 In order to demonstrate the advantages of the cross-linked conductive carbon skeleton structure over the conventional graphene conductive carbon skeleton, the conductivity of the lithium battery negative electrode sheet of Example 1 and the lithium battery negative electrode sheet of Comparative Example 1 were compared. Figure 6 shown.
[0060] It was found that the conductivity of the lithium battery negative electrode sheet of Example 1 was as high as 22.6 S / m, which was 3.3 times that of the lithium battery negative electrode sheet of Comparative Example 1. After the lithium battery negative electrode sheet of Example 1 was placed in a lithium battery electrolyte and soaked for 5 days, its conductivity was still as high as 20.9 S / m, indicating that the integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure of the present invention not only has good electronic conductivity, but also has excellent structural stability.
[0061] Table 1 Comparison of electrochemical cycling performance results
[0062] project <![CDATA[Initial loop surface capacity (mAh / cm -2 ).]]> <![CDATA[Capacity after 200 - cycle charge (mAh / cm -2 )]]> Example 1 5.9 3.5 Comparative Example 1 5.6 0.7 Example 2 4.2 2.6 Comparative Example 2 3.9 0.2
[0063] Technical features not described in the present invention can be achieved through or by adopting existing technologies and will not be described in detail here. Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the scope of protection of the present invention.
Claims
1. An integrated lithium battery negative electrode sheet having a cross-linked conductive carbon skeleton structure, characterized in that: The specific preparation method comprises the following steps: Step S1: dispersing bacterial cellulose in deionized water to prepare a bacterial cellulose dispersion; Step S2: dispersing the lithium ion battery active material into deionized water to prepare an active material dispersion; Step S3: adding the active material dispersion obtained in step S2 dropwise to the bacterial cellulose dispersion obtained in step S1, and stirring in a water bath at room temperature; Step S4: dispersing graphene oxide in deionized water to obtain a graphene oxide dispersion; Step S5: adding the graphene oxide dispersion obtained in step S4 dropwise to the solution obtained in step S3, and continuing to stir in a water bath at room temperature; Step S6: vacuum-filtering the dispersion obtained in step S5, washing and drying to obtain a self-supporting film; Step S7: placing the self-supporting film obtained in step S6 under an inert atmosphere for high-temperature carbonization to obtain an integrated lithium battery negative electrode sheet having a cross-linked conductive carbon skeleton structure.
2. The integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure according to claim 1, characterized in that: In step S1, the dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring, or a combination of at least two or more thereof; In step S2, the dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring, or a combination of at least two of them; In step S4, the dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring, or a combination of at least two or more thereof.
3. The integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure according to claim 1, characterized in that: In the step S1, the concentration of the bacterial cellulose dispersion is 0.1-2.5 mg / mL; In step S2, the concentration of the active material dispersion is 1-10 mg / mL; In the step S4, the concentration of the graphene oxide dispersion is 1-10 mg / mL.
4. The integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure according to claim 1, characterized in that: In the step S2, the active material is any one of silicon, silicon monoxide, tin and bismuth, or a mixture of at least two of them.
5. The integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure according to claim 1, characterized in that: In step S7, the high temperature carbonization temperature range is 700-1100° C. The high temperature carbonization process converts bacterial cellulose into conductive carbon fibers and removes oxygen-containing functional groups on the surface of graphene oxide.
6. The integrated lithium battery negative electrode sheet with a cross-linked conductive carbon skeleton structure according to claim 1, characterized in that: In step S7, the integrated lithium battery negative electrode sheet has a self-supporting structure and does not require the use of a metal current collector; no conductive agent or adhesive is required during the preparation process; and the graphene sheets in the integrated lithium battery negative electrode sheet are cross-linked and the PBFs fibers are arranged throughout, forming a cross-linked conductive carbon skeleton with a multi-porous structure; and the active material in the integrated lithium battery negative electrode sheet is anchored to the cross-linked conductive carbon skeleton through covalent bonds.